Legalizing The Shadow Economy Through Financial Mechanisms: An Imrad-Based Study (American Economist: Journal of Economics Finance and Global Policy, 2026)
The shadow economy remains a persistent challenge for both developed and developing countries, undermining fiscal stability, economic transparency, and social equity. This study investigates the effectiveness of financial mechanisms in facilitating the legalization of shadow economic activities. Using a mixed-method approach combining econometric modeling and comparative policy analysis, the research evaluates the role of tax incentives, financial inclusion, digitalization, and institutional reforms. The findings reveal that financial inclusion and simplified tax regimes significantly reduce informal economic activities, especially when supported by strong governance frameworks. (periodica.org)
Keywords: Shadow economy; Financial mechanisms; Formalization